Transformasi Nilai-Nilai Ahlussunnah Wal Jamaah dalam Dinamika Moderasi Beragama di Langgar Nurul Jamal Desa Marengan Laok Kabupaten Sumenep - Fenny Erdiyani; Halimatus Sa’diyah; Eliyatul Fitriyah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2025)
This study aims to describe the transformation of Ahlussunnah wal Jamaah (Aswaja) values ​​in the dynamics of religious moderation at the Nurul Jamal Mosque (Langgar Nurul Jamal). Using a qualitative, descriptive-empirical approach, data were obtained through observation, interviews, and documentation. Data were then analyzed using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results show that Aswaja values, such as tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i'tidal (justice), are embodied in the yasinan (recitation of the Yasin), sholawatan (prayer), tadarusan (contemplation), istighosah (religious observance), and the commemoration of the Prophet's birthday, reinforcing four indicators of religious moderation: national commitment, tolerance, non-violence, and acceptance of local traditions. The simple, communal, and tradition-based religious patterns of rural communities make these values ​​easily internalized through repeated social habits. Thus, the Nurul Jamal Mosque represents a peaceful, inclusive, and contextual Islamic practice that addresses social change in rural communities.